2010
DOI: 10.1007/s11666-010-9586-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Air Plasma-Sprayed YSZ Functionally Graded Mullite Coatings Investigated via Instrumented Indentation

Abstract: Yttria-stabilized zirconia (YSZ)-mullite multilayer architectures with compositional grading between the bond coat and YSZ top coat are envisioned as solutions to ease their coefficient of thermal expansion mismatch induced stress. In this work, two different types of mullite powder (spray-dried and freezegranulated) and a mullite-YSZ 75/25 vol.% mixture spray-dried powder were employed. Using instrumented indentation with loads between 10 and 500 mN, the role of the powder characteristics on the mechanical be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…To overcome this limitation, an alternate method was followed. This was documented by Cojocaru et al [123], who developed a method to produce as-sprayed crystallized Mullite coatings by using high enthalpy plasma torch and low stand-off distance. This method is based on the capacity of the plasma to locally transfer a high calorific power able to increase momentarily the substrate temperature over 1000 ○ C.…”
Section: Coating Deposition By Vacuum Plasma Sprayingmentioning
confidence: 96%
“…To overcome this limitation, an alternate method was followed. This was documented by Cojocaru et al [123], who developed a method to produce as-sprayed crystallized Mullite coatings by using high enthalpy plasma torch and low stand-off distance. This method is based on the capacity of the plasma to locally transfer a high calorific power able to increase momentarily the substrate temperature over 1000 ○ C.…”
Section: Coating Deposition By Vacuum Plasma Sprayingmentioning
confidence: 96%
“…Cojocaru et al [182] have identified a better match between the elastic modulus, E, and hardness, H, values of the bond coat, and subsequent layers obtained from powders having similar type and size distribution. Das et al [183] have plasma sprayed a mixture of zircon and alumina on a mild steel substrate.…”
Section: Zirconiamentioning
confidence: 99%
“…It is thought that by arranging the smooth change of the mismatch between the thermal expansion coefficients of the composition, the delamination within the FGC structure could be addressed. Other FGCs manufactured using this technique are HAp/TiO 2 , Yttria stabilized zirconia (YSZ)/mullite coats deposited on SiC substrates [53] and tungsten carbide/cobalt (WC/Co) FGC [54].…”
Section: Thermal Sprayingmentioning
confidence: 99%